SYSTEM DESIGN INTERVIEW : AN INSIDER'S GUIDE - Xu, Alex (Byte Code LLC, 2020)
System design interviews are the most difficult to tackle of all technical interview questions. This book is Volume 1 of the System Design Interview - An insider’s guide series that provides a reliable strategy and knowledge base for approaching a broad range of system design questions. This book provides a step-by-step framework for how to tackle a system design question. It includes many real-world examples to illustrate the systematic approach, with detailed steps that you can follow